AN ANALYSIS OF EDNA PONTELIER’S SELF ACTUALIZATION ACT IN KATE CHOPIN’S THE AWAKENING NOVEL - Risma Kartika Dewi (Fakultas Sastra Universitas Gresik, 2020)
This thesis was explained about an analysis of Edna Pontelier’s self actualization act on psychoanalogical approach in Kate Chopin’s The Awakening novel. Based on feminist perspective which critiquing the patriarchal ideology of Western society especially in America, during Victorian Era. I am getting inspired to write about this topic because i am a woman who has experience of being oppressed due to i was born as a woman. I also have experienced the debilitating sexism and devaluation of my gender through the social institution of marriage and the historical and legal institutionalization of women’s rights and property.I have learned that I was not alone in this experience and that many women i have known felt much the same way based on Kate Chopin experiences as a gendered woman in her society. I realized if i have the same feelings of helplessness, determination, fear, sadness, and mostly frustration with an unbalanced and unequal way of life. Understanding and sharing this experience with other women from the present to the past created a passion inside me to share that information with men and women of all races and classes. This is one of the reasons why this research is so incredibily important to me and i hope that it will have the same impact too for those who are in need.Key words : Psychoanalogical Approach, Victorian Era, The Awakening